Origin and Pathways of Dissolved Organic Carbon in a Small Catchment in the Lena River Delta ... - Stolpmann, Lydia; Mollenhauer, Gesine; Morgenstern, Anne; Hammes, Jens S.; Boike, Julia; Overduin, Pier; Grosse, Guido (Humboldt-Universität zu Berlin, 2022)
The Arctic is rich in aquatic systems and experiences rapid warming due to climate change. The accelerated warming causes permafrost thaw and the mobilization of organic carbon. When dissolved organic carbon is mobilized, this DOC can be transported to aquatic systems and degraded in the water bodies and further downstream. Here, we analyze the influence of different landscape components on DOC concentrations and export in a small (6.45 km2) stream catchment in the Lena River Delta. The catchment includes lakes and ponds, with the flow path from Pleistocene yedoma deposits across Holocene non-yedoma deposits to the river outlet. In addition to DOC concentrations, we use radiocarbon dating of DOC as well as stable oxygen and hydrogen isotopes (δ18O and δD) to assess the origin of DOC. We find significantly higher DOC concentrations in the Pleistocene yedoma area of the catchment compared to the Holocene non-yedoma area with medians of 5 and 4.5 mg L−1 (p < 0.05), respectively. When yedoma thaw streams with ...